2018
DOI: 10.1111/nyas.13588
|View full text |Cite
|
Sign up to set email alerts
|

Precision medicine in diabetes: an opportunity for clinical translation

Abstract: Metabolic disorders present a public health challenge of staggering proportions. In diabetes, there is an urgent need to better understand disease heterogeneity, clinical trajectories, and related comorbidities. A pressing and timely question is whether we are ready for precision medicine in diabetes. Some biological insights that have emerged during the last decade have already been used to direct clinical decision making, especially in monogenic forms of diabetes. However, much work is necessary to integrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 120 publications
0
30
0
1
Order By: Relevance
“…DM, being a major public health challenge and a heterogeneous disease, calls for better understanding of its pathogenesis, clinical manifestation, comorbidities, and future complications particularly dementia. Despite the heterogeneity of pathogenesis, DM is characterized by insulin resistance or relative insulin deficiency in the presence of hyperglycemia and represented with internal glycemic index parameters like HbA1c, fasting blood sugar, and so on [87]. Several observational studies from high-income countries have found environmental effects influencing T2DM.…”
Section: Disease Management By Lifestyle Modifications and Integrativmentioning
confidence: 99%
“…DM, being a major public health challenge and a heterogeneous disease, calls for better understanding of its pathogenesis, clinical manifestation, comorbidities, and future complications particularly dementia. Despite the heterogeneity of pathogenesis, DM is characterized by insulin resistance or relative insulin deficiency in the presence of hyperglycemia and represented with internal glycemic index parameters like HbA1c, fasting blood sugar, and so on [87]. Several observational studies from high-income countries have found environmental effects influencing T2DM.…”
Section: Disease Management By Lifestyle Modifications and Integrativmentioning
confidence: 99%
“…The variety of different hybrid forms of DM, including latent autoimmune disease of adults (LADA) and ketosis-prone diabetes (KPD), is suggestive of biological alterations. In diabetes care, the scope of precision diabetes applies both to the more common forms of diabetes, such as T1DM and T2DM, and to the relatively rare subtypes of diabetes, such as monogenic diabetes [4].…”
Section: Precision Medicine In Diabetes Mellitusmentioning
confidence: 99%
“…Knowledge of an accepted classification of DM is prudent to a good understanding of the clinical application of precision medicine in diabetes care. With this in mind, according to the American Diabetes Association (ADA) Standards of Medical Care in Diabetes-2019 [4], DM can be classified into the following general categories: [5].…”
Section: Precision Medicine In Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, genome-wide-significant and validated SNPs account for 10-15% of overall heritability of T2D susceptibility [10]. This "missing heritability" led to next generation sequencing of whole exomes and genomes to identify rare variants with presumably larger genetic effect sizes [11].…”
Section: Genomics Of T2dmentioning
confidence: 99%